Clinico-bacterial correlation of bacterial index in Hansen’s disease (Journal of Pathology of Nepal, 2016)
Background: Leprosy has a broad spectrum of clinical manifestations. Clinical information along with Bacterial evidence is necessary to achieve accurate diagnosis. The present study was carried out to nd out clinical and bacterial correlation in various presentations according to Ridley Jopling classi cation of Hansen’s Disease. Materials and Methods: It was a hospital based cross-sectional comparative study of 72 leprosy patients over a period of 1 year and it’s clinico-Bacterial correlation was done with the help of Slit Skin Smear and clinical classi cation. Results: This study included 72 leprosy patients at various stages according to Ridley Jopling classi cation. Maximum cases belonged to Borderline Tuberculoid leprosy 28(38.88%) followed by Tuberculoid leprosy 15(20.83%). Slit Skin Smear showed 12(42.85%) of Borderline Tuberculoid and 3(20%) of Tuberculoid cases had disparity and didn’t match corresponding clinical subtype. Conclusion: Clinical features along with Bacterial index is useful in making accurate diagnosis so that appropriate treatment could be started and hence deformity and disability could be prevented.